Diet and female fertility: a population-based study re-evaluating the need for prescriptive dietary patterns - Alesi, Simon; Grieger, Jessica A.; Teede, Helena; Hébert, James R.; Moss, R. Kendal; Price, Sherry; Hodge, Allison; Moran, Lisa; Mousa, Aya (Frontiers in Nutrition, 2025)
IntroductionDiet may impact female fertility via inflammatory pathways, but the value of specific anti-inflammatory dietary indices compared with general healthy eating guidelines is unclear. We examined associations between different measures of dietary inflammation and diet quality with female infertility in a large population-based study.MethodsData for 5,489 participants from the Australian Longitudinal Study on Women’s Health were analysed (1973–1978 cohort assessed in 2009, at 31–36 years old; n = 1,289 fertility problems, n = 4,200 no fertility problems). Dietary inflammatory potential was assessed using the energy-adjusted dietary inflammatory index (E-DII™). Diet quality was examined using the dietary guideline index (DGI) and principal component analysis (PCA) for a posteriori patterns. Cross-sectional associations between these indices and self-reported fertility problems were assessed using logistic regression, adjusted for relevant covariates.ResultsA diet with greater inflammatory potential was associated with higher odds of self-reported fertility problems (adjusted odds ratio (aOR) per 1-unit increase in E-DII: 1.13, 95% confidence interval (CI): 1.06, 1.19), with significant differences between the highest and lowest E-DII quartiles (aOR: 1.53, 95%CI: 1.23, 1.90). Higher dietary quality was associated with lower odds of self-reported fertility problems (aOR per 1-unit increase in DGI: 0.99, 95% CI: 0.99, 0.99), including when comparing highest and lowest DGI quartiles (aOR: 0.76, 95% CI: 0.61, 0.95). In PCA, consumption of a Mediterranean-style dietary pattern was associated with lower odds of self-reported fertility problems (aOR: 0.92, 95% CI: 0.88, 0.97), including when comparing highest and lowest quartiles (aOR: 0.70, 95% CI: 0.57, 0.85).DiscussionOur data suggest that following a generally healthy diet is associated with improved female fertility, whether by adherence to low inflammatory potential diets, Mediterranean-style dietary patterns or national dietary guidelines. These findings suggest that general, guideline-based healthy eating can support female fertility and may offer a flexible alternative to more prescriptive dietary approaches.